Sustainable technology and business innovation framework: A comprehensive approach - Maja Levi-Jakšić; Jovana Rakićević; Milica Jovanović (Amfiteatru Economic Journal, 2018)
Despite of the rising awareness of the urgency in finding more efficient and effective ways to achieve sustainable development, comprehensive and consistent meaning is still elusive both in theory and practice. The aim of this paper is to create a more structured theoretical framework related to macro and micro perspectives of sustainable development, relevant also to enhancing sustainable practices. We here propose a comprehensive framework model for structuring multiple sustainability principles and practices, detected in the literature as different sustainability categories related to both macro and micro perspectives of sustainability in the economy and society. The focus is on relevant sustainability principles of technology and business innovation in relation to basic technology and business innovation models as a contribution to less investigated theoretical aspects of sustainable business development. We developed a set of related matrices indicating the relevant roles and relationships between these principles in achieving sustainable business goals related to sustainable economy dimensions. Finally, the paper shows that the proposed Related Matrices Framework fulfils the main objective set in the initial research stages, i.e. to be of both theoretical and practical relevance. As a contribution to the theory it meets the need of building a structured, integrated, comprehensive model that serves the needs of better understanding different sustainability of macro and micro categories, indicating mutual relations and influences. In a practical sense, it can be used as a tool to support the management of change in companies oriented at achieving sustainable business goals based on sustainable technology and business innovation.
Keywords: Q01; Q56; O32; M21; 330; sustainable economy dimension; sustainable business development goal; sustainable technology and business innovation; business model innovation